(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
This article examines the essence and theory of the green economy of the relationship between economic management and the environmental environment. Moreover, the limitations of natural resources have been studied and the need for recycling are global problems, as well as emission management, waste management, transportation, collection, waste disposal, recycling and downcycling